An assessment of public experiences and expectations with physicians: a cross sectional study from Karachi, Pakistan - Hammad Atif Irshad; Muhammad Umar Mahar; Arshia Jahangir; Syed Roohan Aamir; Muhammad Abdullah Jamil; Khizer Ahsan; Maliha Taufiq; Abdullah Ahmed; Shilpa Golani; Sehba Amir; Wasila Gul Kakar; Abida Ali; et al. (BMC, 2024)
Abstract Background Although physicians are highly regarded members of society, patients are not always satisfied with their care, suggesting a mismatch between the public's expectations and reality. Thus, the aim of this study was to determine the public's expectations regarding roles and responsibilities of a physician, to assess patient experiences, and to evaluate factors associated with the two outcomes. Methods A cross-sectional study was conducted via face-to-face structured interviews from July 14th to August 2nd, 2023, in Karachi, Pakistan. The study sample comprised 424 consenting adults enrolled by visiting public spaces (malls, parks, hospitals, and residential areas). A modified version of 'Exceptionally Good Doctor Likert scale', and 'Patient Picker-15' (PPE-15) questionnaires was used. The Likert and PPE-15 sections were scored through pre-decided criteria for expectations and experience, respectively, and categorized using a median cut-off into high and low expectations and negative and positive experiences, respectively for simple and multivariable logistic regression. Results A median score of 30.5/ 34 (IQR = 3.3) was found for expectations and 4/ 14 (IQR = 4) for experiences. Significant factors associated with expectations were older age groups (OR = 4.54 [1.18-17.50]) and higher monthly household incomes (0.40 [0.20-0.79]), while the odds of negative experiences were lower after visits to emergency departments (0.38 [0.18-0.84]) and private health care centers (0.31 [0.13-0.70]). Conclusion These results suggest that the public has high expectations from physicians, however their experiences are not always positive. Initiatives to develop a patient-centric ethos are needed for which we outline recommendations to both the public and physicians, respectively.